Organizational and environmental factors with the mediating role of e-commerce and SME performance - Arsalan Hussain; Arfan Shahzad; Rohail Hassan (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
The study investigates the mediating role of e-commerce through organizational and environmental factors with small and medium enterprises (SMEs) performance. The study follows a cross-sectional survey method approach. The study's theoretical foundation is based on the resource-based view (RBV) and diffusion of innovation (DOI) theory. The current research identifies four manufacturing SMEs' strata based on participation in the country's exports using a stratified proportional random sampling technique. The research questionnaires were distributed among 700 top and middle-level managers of manufacturing SMEs. The data were analyzed by applying partial least square structural equational modeling (PLS-SEM) to examine the relationship between the exogenous, mediator, and endogenous variables. The finding reveals that top management support and competitive pressure have a significant positive impact on the use of e-commerce direct and mediation. At the same time, the adoption cost and government support have an insignificant impact on e-commerce usage. This study results can be used to enhance the use of e-commerce in Pakistan's manufacturing SMEs to improve the country's overall exports.
Keywords: 650; environmental; firm performance; manufacturing SMEs; organizational; use of e-commerce